Analisis Faktor-Faktor Store Atmosphere Terhadap Impulse Buying Pada The Warong Distorsi Di Tenggarong - Juwita Andriani; Awang Yacoub Luthman; Ilham Ilham (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:The purpose of this study was to determine and analyze the influence of store atmosphere factors on impulse buying. The data used is primary data. This research method uses sampling aksidental. Samples were examined as many as 122 respondents. The number of independent variables studied were 4 namely exterior (exterior), general interior (inside), store layout (store layout), interior display (in store display), and with 1 dependent variable namely impulse buying (unexpected purchase) . In this study using an analytical tool, Factor Analysis. From the results of this study states that the first hypothesis in this study which states that